Integration of Technology and Governance in Indonesian Schools: Toward a Smart School Ecosystem - Dadang Rahman Munandar (STAI Hubbulwathan Duri, 2025)
This study investigates the integration of technology and governance in education management as a strategic effort to establish a smart school ecosystem. The increasing reliance on digital tools necessitates that schools adopt systems aligned with transparent, accountable, and participatory governance principles. A descriptive qualitative approach was employed to explore how digital technologies and governance practices are implemented and mutually reinforce one another in educational settings. Data were gathered through interviews, observations, and documentation from secondary schools in Bandung identified as smart schools due to their use of digital learning and management systems. The findings indicate that the adoption of Information and Communication Technology (ICT) significantly improves efficiency, transparency, and accessibility in school management. Initiatives such as online learning platforms, digital assessment tools, and Bandung’s SaKOJA program enhance the quality of education and widen access, including for students with disabilities. Furthermore, ICT integration strengthens administrative processes, fosters collaboration among stakeholders, and supports responsive and flexible learning environments. The synergy between technology and governance plays a crucial role in driving sustainable educational transformation. Schools that adopt ICT-driven governance models are better positioned to create inclusive, adaptive, and future-ready learning environments.